Spectrophotometric Determination of Strontium with Dibromo-p-chloro-chlorophosphonazo - Wang, Qing-Shuang; Zhai, Qing-Zhou; Zhang, Xiao-Xia; Li, Ji-Qiang (Asian Journal of Chemistry, 2012)
Based on the complex reaction of dibromo-p-chloro-chlorophosphonazo (DBC-CPA) with strontium in the medium of 6.32 × 10-2 mol/L hydrochloric acid, this work established a simple, rapid and sensitive method for the determination of strontium by spectrophotometry. The maximum absorption peak of Sr2+-(DBC-CPA) complex locates at 620 nm. At this wavelength, Beer's law is obeyed over the range of 0-2 μg/mL and its regression equation is: A = 0.237 C (C: μg/mL) + 0.008, with a correlation coefficient of 0.9991. The apparent molar absorption coefficient of the method is e620 nm = 2.11 × 104 L mol-1 cm-1 and its detection limit is 0.234 μg/ mL. The composition of complex is 1 : 2 [nSr2+: n(DBC-CPA)] obtained respectively by molar ratio method and the equimolar continuous variation method. The present method has been successfully applied to the determination of strontium contents in rain water and lake water. The relative standard deviation of 13 determinations was 1.28-3.90 % and the recovery of the standard addition was 95.32-97.12 %.